Land compensation and land conflict resolution in Zimbabwe : challenges and prospects for the second republic’s relations with the west - P Sixpence; P Chigora (Journal of Public Administration and Development Alternatives, 2020)
On 29 July 2020, the government of Zimbabwe and representatives of the former white farmers signed the Global Compensation Agreement (GCA) in which the government committed to paying a total of USD3.5billion to the farmers for the developments instituted on the farms before the Fast Track Land Reform Programme (FTLRP). The deal was guided by section 72(3) of the 2013 constitution of Zimbabwe. The GCA provides for the establishment of various joint committees for the evaluation of the developments in question, the fundraising process, and the payment procedures. While this is seen as being a show of commitment by the government of Zimbabwe to close the land chapter amicably, there are mixed voices on the development notwithstanding that the decision was accepted by 94.49% of Zimbabweans who voted in the 2013 referendum (ZEC 2013). It is, therefore, the purpose of this article is to look at the challenges and prospects of the land compensation agreement as a conflict resolution move pursued by Zimbabwe’s second republic and its implications for relations with Western countries and institutions. To achieve this, the article depended upon both primary and secondary sources of qualitative research. The primary sources used in this article are mainly the pieces of legislation (both colonial and post-colonial), reports by various commissions, and the Zimbabwe constitution. Secondary sources, mainly published material, media reports, official institutional reports and websites, and interviews were used in this research.